Prevalence and distribution of Angiostrongylus cantonensis (Nematoda, Angiostrongylidae) in Achatina fulica (Mollusca, Gastropoda) in Baixada Santista, Sao Paulo, Brazil - Guerino, Laura Rocha [UNESP]; Pecora, Iracy Lea [UNESP]; Miranda, Marcel Sabino; Aguiar-Silva, Cryslaine; Carvalho, Omar dos Santos; Caldeira, Roberta Lima; Silva, Reinaldo Jose da [UNESP] (Soc Brasileira Medicina Tropical, 2017)
Introduction: Angiostrongylus cantonensis causes eosinophilic meningoencephalitis in humans. Worldwide expansion of this nematode is linked to the dispersion of their hosts. This study aimed to determine the prevalence of A. cantonensis infection in Achatina fulica in the nine municipalities that make up Baixada Santista, Sao Paulo, Brazil. Methods: Angiostrongylus cantonensis larvae were analyzed using optical microscopy. We performed polymerase chain reaction and restriction fragment length polymorphism using restriction endonuclease ClaI, directed to the internal transcribed spacer region 2 of A. cantonensis larval DNA. Results: Of the 540 snails analyzed, 117 (21.7%) were infected by A. cantonensis. For morphological and morphometric analyses, 60 larvae were used. Second-stage larvae were, on average, 358.2 mu m long and 26.4 mu m wide, while third-stage larvae were, on average, 450 mu m long and 21.12 mu m wide. The tails of the larvae ended in a fine tip. Conclusions: All municipalities comprising Baixada Santista had A. fulica that were naturally infected with A. cantonensis. All of the observed characteristics were typical of the species.
Keywords: Rat lungworm; Giant African snail; Eosinophilic meningitis; Nematode; Emerging parasitosis